Proceedings of the international school of Physics “Enrico fermi” (Course CLXV) - Broglia, R. A (IOS Press, 2013)
”One of the great unsolved problems of science is the prediction of the threedimensional structure of a protein from its amino acid sequence: the folding problem”. Thus wrote Sir Alan Fehrst, an illustrious scientist from Cambridge, a few years ago. But because, according to another Cambridge scholar, Lord Rutherford : “science is either physics or it is stamp collection”, the “protein folding problem” is also one of the great unsolved problems of physics. This is the reason why the Italian Physical Society organized the present “Enrico Fermi” Summer School, on the premises of Villa Monastero, where Enrico Fermi lectured for the last time in Italy (summer 1954) before his untimely death on November 29th of that year.